Korporatisme Pedesaan Orde Baru: Program Tebu Rakyat Intensifikasi (TRI) di Wilayah Kerja Pabrik Gula Mojo Sragen, 1975-1998 - Prima Dwianto (Lembaran Sejarah, 2014)
The Indonesian government has radically altered the structure of the national sugar industry by issuing Presidential Instruction no 9/1975 on the People’s Sugarcane Intensification Program (TRI) in order to increase sugar productivity. The dependence on the production process to sugar factories was replaced with the production process of the farmers from planting to harvesting. This research intends to document the socio-economic effects of the TRI program on farmers within the Mojo Sugar Factory work area in Sragen, Central Java, between 1975 until 1998. The result of the research has shown that farmers south of the Bengawan Solo river were resistant to the TRI program in favor of more lucrative rice farming. These farmers conducted social protests such as sugarcane field burnings. Farmers that lived north of the river supported the TRI program because planting sugarcane on non-irrigated fields was more profitable than planting other crops. This research shows that the TRI program has positively benefited to some farmers, a conclusion that is not shared by previous researches that point to only negative effect of the program.